Kinerja Pelayanan Publik Di Dinas Sosial Kota Ambon - Devita Sari; Z. A. Rengifurwarin; Julia Th Patty (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
The purposes to analyze and explain an overview of the performance of Public Services, as well as the supporting and inhibiting factors in the Ambon City Social Agency. The informants of this study were 12 people. The data needed in this study were collected through observation, interviews, and documentation. The data were collected, processed, and analyzed by using descriptive qualitative analysis techniques. The results of this study indicate that the performance of public services at the Ambon City Social Service is quite good, but not optimal as a whole, such as: 1) Service quality, 2) Service quantity, 3) Service accuracy, 4) Service effectiveness, 5) Service independence on the side other supporting factors are, 1) Employee Salary Factor, 2) Employee Work Environment Factor, 3) Employee Work Culture Factor, 4) Employee Work Motivation Factor While the inhibiting factors are: 1) Employee Work Discipline Factor, and 2 ) Employee Job Satisfaction Factor, the implication of this research, that if you want to improve the performance of public services at the Ambon city social service office, it is necessary to optimally develop the supporting factors, and improve the inhibiting factors